Changes in sleep pattern, sense of time and digital media use during COVID‐19 lockdown in Italy. (15th May 2020) - Cellini, Nicola; Canale, Natale; Mioni, Giovanna; Costa, Sebastiano
Abstract: Italy is one of the major COVID‐19 hotspots. To reduce the spread of the infections and the pressure on Italian healthcare systems, since March 10, 2020, Italy has been under a total lockdown, forcing people into home confinement. Here we present data from 1, 310 people living in the Italian territory ( M age = 23.91 ± 3.60 years, 880 females, 501 workers, 809 university students), who completed an online survey from March 24 to March 28, 2020. In the survey, we asked participants to think about their use of digital media before going to bed, their sleep pattern and their subjective experience of time in the previous week (March 17–23, which was the second week of the lockdown) and up to the first week of February (February 3–10, before any restriction in any Italian area). During the lockdown, people increased the usage of digital media near bedtime, but this change did not affect sleep habits. Nevertheless, during home confinement, sleep timing markedly changed, with people going to bed and waking up later, and spending more time in bed, but, paradoxically, also reporting a lower sleep quality. The increase in sleep difficulties was stronger for people with a higher level of depression, anxiety and stress symptomatology, and associated with the feeling of elongation of time. Considering that the lockdown is likely to continue for weeks, research data are urgently needed to support decision making, to build public awareness and to provide timely and supportive psychosocial interventions.